2001
DOI: 10.1021/bi015546s
|View full text |Cite
|
Sign up to set email alerts
|

Subsite Specificity of Memapsin 2 (β-Secretase):  Implications for Inhibitor Design

Abstract: Memapsin 2 is the protease known as beta-secretase whose action on beta-amyloid precursor protein leads to the production of the beta-amyloid (Abeta) peptide. Since the accumulation of Abeta in the brain is a key event in the pathogenesis of Alzheimer's disease, memapsin 2 is an important target for the design of inhibitory drugs. Here we describe the residue preference for the subsites of memapsin 2. The relative k(cat)/K(M) values of residues in each of the eight subsites were determined by the relative init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
166
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(177 citation statements)
references
References 15 publications
10
166
1
Order By: Relevance
“…When mutant substrate ST-LA was used, in which Leu at the P1 position was replaced by Ala, cleavage efficiency was reduced to 40% compared with the wild-type substrate (ST-WT), suggesting that the Leu residue in the ST6Gal I peptide is recognized as a preferable amino acid at the P1 position. This result is consistent with those reported previously by others (21,22); Leu at the P1 position in the APP sequence is recognized preferentially by BACE1.…”
Section: ␣26-sialyltransferase Cleavage By Bace1supporting
confidence: 94%
See 1 more Smart Citation
“…When mutant substrate ST-LA was used, in which Leu at the P1 position was replaced by Ala, cleavage efficiency was reduced to 40% compared with the wild-type substrate (ST-WT), suggesting that the Leu residue in the ST6Gal I peptide is recognized as a preferable amino acid at the P1 position. This result is consistent with those reported previously by others (21,22); Leu at the P1 position in the APP sequence is recognized preferentially by BACE1.…”
Section: ␣26-sialyltransferase Cleavage By Bace1supporting
confidence: 94%
“…BACE1 Cleaved ST6Gal I-derived Peptide between Leu 37 and Gln 38 -We confirmed that the secreted ST6Gal I starts at Glu 41 in vivo as well as in cultured cells (19), but in vitro studies by others (21,22) on BACE1 cleavage site preference showed that Lys 40 residue at the P1 position is not a preferable amino acid for BACE1 cleavage. We therefore analyzed BACE1-dependent cleavage of a peptide substrate, DYEAL-TLQAKEFQMPKSQE, which corresponds to Asp 31 ϳGlu 49 of ST6Gal I sequence.…”
Section: Secreted St6gal I From the Cells Starts At Glusupporting
confidence: 59%
“…Another peptidic substrate with a much lower K m has been reported recently (25), and we were able to advance mechanistic studies using this substrate and HPLCbased detection method. Under our assay conditions, the latter substrate was cleaved by BACE with k cat of 0.32 Ϯ 0.02 s Ϫ1 and…”
Section: Resultsmentioning
confidence: 80%
“…When the ␤-secretase inhibitor OM00 -3 was used, Alexa 488-labeled M2 ED (1 M) was preincubated with OM00 -3 (12.4 M) for 30 min at 37°C before adding to cells. The inhibition constant of OM00 -3 for M2 ED at pH 7.0 was determined using the previously described method (15). The internalization of Alexa 488-labeled recombinant M2 ED also was studied by flow cytometry as follows.…”
Section: Methodsmentioning
confidence: 99%
“…The Swedish mutation at the P 2 -P 1 positions, from Lys-Met to Asn-Leu, enhances the catalytic efficiency by about 60-fold, increases A␤ production, and manifests an early onset form of AD. The specificity of memapsin 2 for all eight substrate residues has been determined previously (15). Memapsin 2 is glycosylated by three N-linked oligosaccharides (16).…”
mentioning
confidence: 99%